PENGARUH KOMPENSASI FINANSIAL LANGSUNG TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Pada Ratu Swalayan Dampit Kabupaten Malang) - Denny Irawati Agustin (Universitas muhammadiyah malang, 2018)
This study aim describing direct financial compensation and turnover intention in Ratu Supermarket, Dampit, Malang Regency, determining influence of direct financial compensation on employees’ turnover intention, and identifying job satisfaction that mediates the influence of direct financial compensation on the turnover intention in Ratu Supermarket, Dampit,Malang Regency.The population was all employees amounted to 32 people. The sampling technique used was population sample, in which all population was used as the sample.Data collection techniques used interviews, questionnaires and documentation. The data were analyzed by using Path Analysis and Sobel Test. The result of the study showed that direct financial compensation had a good criteria whereas job satisfaction had a high criteria, and turnover intention have a high criteria. From the Path Anlysis and Sobel Test, it indicates that direct financial compensation had a significant influence on turnover intention, and the other Path Anlysis showed that direct financial compensation and job satisfaction had significant influence on turnover intention. The result of the analysis confirmed that job satisfaction could mediate direct financial compensation that influence the turnover intention in Ratu Supermarket, Malang Regency.